Assessing periodontitis in populations: a systematic review of the validity of partial‐mouth examination protocols. (8th October 2013) - Tran, Duong T.; Gay, Isabel; Du, Xianglin L.; Fu, Yunxin; Bebermeyer, Richard D.; Neumann, Ana S.; Streckfus, Charles; Chan, Wenyaw; Walji, Muhammad F.
Abstract: Objective: To estimate bias associated with partial‐mouth periodontal examination (PMPE) protocols regarding estimates of prevalence, severity and extent of clinical attachment loss (CAL), pocket depth (PD) and gingival recession (REC). Material and Methods: A search was made for articles published in English, from 1946 to 2012, which compared PMPE versus full‐mouth periodontal examination protocols for CAL or PD ≥ 4 mm or REC ≥3 mm thresholds. PMPE protocols were evaluated for sensitivity of estimates of periodontitis prevalence, relative biases for severity and extent estimates. Results: A review of the literature identified 12 studies which reported 32 PMPE protocols. Three PMPE protocols which had sensitivities ≥85% and relative biases ≤0.05 in absolute values for severity and extent estimates were as follows: (1) half‐mouth six‐sites, (2) diagonal quadrants six‐sites and (3) full‐mouth mesiobuccal–midbuccal–distobuccal (MB–B–DB). Two other PMPE protocols (full‐mouth and half‐mouth mesiobuccal–midbuccal–distolingual) performed well for prevalence and severity of periodontitis; however, their performance in estimates of extent was unknown. Conclusions: Among the 32 PMPE protocols listed, the half‐mouth six‐sites and full‐mouth MB–B–DB protocols had the highest sensitivities for prevalence estimates and lowest relative biases for severity and extent estimates.